2014
DOI: 10.1021/jp505746x
|View full text |Cite
|
Sign up to set email alerts
|

Linking Electrostatic Effects and Protein Motions in Enzymatic Catalysis. A Theoretical Analysis of Catechol O-Methyltransferase

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 79 publications
0
18
0
Order By: Relevance
“…In particular, the methyl transfer reaction catalyzed by catechol O-methyl transferase (COMT) proceeds from charged reactants (catecholate and S-adenosyl methionine) to neutral products. In that case it was found that the transmission coefficient for the enzymatic TS defined using a simple antisymmetric transfer coordinate was quite high ( 52 ). In addition, the quality of the RC, determined from the committor histogram, was not noticeably improved when optimized, including also a collective environmental coordinate.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the methyl transfer reaction catalyzed by catechol O-methyl transferase (COMT) proceeds from charged reactants (catecholate and S-adenosyl methionine) to neutral products. In that case it was found that the transmission coefficient for the enzymatic TS defined using a simple antisymmetric transfer coordinate was quite high ( 52 ). In addition, the quality of the RC, determined from the committor histogram, was not noticeably improved when optimized, including also a collective environmental coordinate.…”
Section: Discussionmentioning
confidence: 99%
“…The activation barriers of the methyl transfer reaction for COMT and its Y68A mutant were evaluated by the empirical valence bond (EVB) method . This method, which is described in details elsewhere and in the Supporting Information, provides a powerful way of obtaining reliable activation free energies, while taking into account the full protein flexibility and configuration space. All the simulations were carried out by the MOLARIS package using the ENZYMIX force field.…”
Section: Methods and Computational Approachesmentioning
confidence: 99%
“…who have proposed that electrostatic preorganization has an important contributions to the rate enhancement in the reaction catalyzed by COMT (see also recent work in Ref. ). Although this study was not done at a sufficiently quantitative level it has provided a reasonable analysis.…”
Section: Introductionmentioning
confidence: 96%
“…S2). Numerous computational studies have attempted to understand the origin of the experimentally measured inverse KIE (15)(16)(17)(18)(27)(28)(29)(30)(31)(32)(33). Using the available X-ray structures for the soluble form of COMT, Lau and Bruice (16) applied classical molecular dynamics (MD) to identify a small subset of ground state structures that bring the donor and acceptor atoms closer than van der Waals distances.…”
mentioning
confidence: 99%